Relationship Between Resting Heart Rate and Microalbuminuria in Adults With Hypertension: National Health and Nutrition Examination Survey 2009–2018 - Peng, Xiaodong; Li, Yukun; Wang, Xuesi; Ruan, Yanfei; Liu, Nian (Frontiers in Cardiovascular Medicine, 2022)
Background: The impact of elevated resting heart rate on early-stage renal dysfunction, manifesting as microalbuminuria, in hypertension is unclear. This study aimed to analyze the association between resting heart rate and microalbuminuria in patients with hypertension according to their blood pressure status. In addition, the effect of antihypertensive agents on this relationship was evaluated. Methods and Results: We searched the National Health and Nutrition Examination Survey for eligible participants from 2009 to 2018. Data on key parameters such as age, sex, blood pressure, heart rate, albumin creatinine ratio, and medication were collected for analysis. Subsequently, participants were classified according to the heart rate quartile and blood pressure status for subgroups assessment. A total of 5,692 participants were enrolled in this study. After adjusting the confounding factors, there was a linear association between resting heart rate and microalbuminuria in patients with hypertension (OR 1.184 [per 1 SD]; 95% CI: 1.101, 1.274; P<0.001). However, the association between elevated resting heart rate and microalbuminuria was not significant in patients with uncontrolled hypertension (OR 1.092 [per 1 SD]; 95% CI: 0.935, 1.275; P=0.269). Further, the use of β-blockers is associated with a reduced prevalence of microalbuminuria by decreasing the heart rate (OR 0.928; 95% CI: 0.896, 0.958; Indirect effect). However, the total effect of β-blockers on the incidence of microalbuminuria was detrimental (OR 1.292; 95% CI: 1.073, 1.555; P=0.002). Conclusion: Elevated resting heart rate is associated with a high risk of microalbuminuria in untreated patients and patients with controlled hypertension. Although there is a linear association between heart rate and microalbuminuria, the use of β-blockers exhibits a significantly increase in the prevalence of microalbuminuria in hypertension.